THE EFFECT OF SUCCESSOR CHARACTERISTICS ON SUCCESSION PLANNING - Martini, Luh Kadek Budi; Dewi, I Gusti Ayu Manuati (Universitas Brawijaya, Indonesia, 2020)
The main objective of this study was to determine the effect of successor characteristics on the succession planning of family companies in Bali. This research was conducted at family companies on the textile and weaving industries in Bali, both small, medium and large scale, with the condition that it has done minimal succession in the second generation. Successor characteristics and succession planning were measured by a qualitative approach using a Likert scale. Then the data were analyzed using Partial Least Square Path Modeling (PLS-PM). The results of the study found that the characteristics of successors had a positive and significant effect on succession planning. It meant that the better the successor's characteristics, the better succession planning would be. Willingness to take over the management of the family business will strengthen the commitment of all family members. Suggestions for further researchers, this family business research is limited to those engaged in the textile and weaving industry, so it needs to be expanded again for family businesses engaged in other business sectors.